Defining pediatric polypharmacy: A scoping review. - Paul M Bakaki; Alexis Horace; Neal Dawson; Almut Winterstein; Jennifer Waldron; Jennifer Staley; Elia M Pestana Knight; Sharon B Meropol; Rujia Liu; Hannah Johnson; Negar Golchin; James A Feinstein; et al. (PLoS ONE)
Objectives Lack of consensus regarding the semantics and definitions of pediatric polypharmacy challenges researchers and clinicians alike. We conducted a scoping review to describe definitions and terminology of pediatric polypharmacy. Methods Medline, PubMed, EMBASE, CINAHL, PsycINFO, Cochrane CENTRAL, and the Web of Science Core Collection databases were searched for English language articles with the concepts of "polypharmacy" and "children". Data were extracted about study characteristics, polypharmacy terms and definitions from qualifying studies, and were synthesized by disease conditions. Results Out of 4,398 titles, we included 363 studies: 324 (89%) provided numeric definitions, 131 (36%) specified duration of polypharmacy, and 162 (45%) explicitly defined it. Over 81% (n = 295) of the studies defined polypharmacy as two or more medications or therapeutic classes. The most common comprehensive definitions of pediatric polypharmacy included: two or more concurrent medications for ≥1 day (n = 41), two or more concurrent medications for ≥31 days (n = 15), and two or more sequential medications over one year (n = 12). Commonly used terms included polypharmacy, polytherapy, combination pharmacotherapy, average number, and concomitant medications. The term polypharmacy was more common in psychiatry literature while epilepsy literature favored the term polytherapy. Conclusions Two or more concurrent medications, without duration, for ≥1 day, ≥31 days, or sequentially for one year were the most common definitions of pediatric polypharmacy. We recommend that pediatric polypharmacy studies specify the number of medications or therapeutic classes, if they are concurrent or sequential, and the duration of medications. We propose defining pediatric polypharmacy as "the prescription or consumption of two or more distinct medications for at least one day". The term "polypharmacy" should be included among key words and definitions in manuscripts.